Coordinated Reversal of Flagellar Motors on a Single Escherichia coli Cell - Terasawa, Shun (The Biophysical Society, 2011)
An Escherichia coli cell transduces extracellular stimuli sensed by chemoreceptors to the state of an intracellular signal molecule, which regulates the switching of the rotational direction of the flagellar motors from counterclockwise (CCW) to clockwise (CW) and from CW back to CCW. Here, we performed high-speed imaging of flagellar motor rotation and show that the switching of two different motors on a cell is controlled coordinatedly by an intracellular signal protein, phosphorylated CheY (CheY-P). The switching is highly coordinated with a subsecond delay between motors in clear correlation with the distance of each motor from the chemoreceptor patch localized at a cell pole, which would be explained by the diffusive motion of CheY-P molecules in the cell. The coordinated switching becomes disordered by the expression of a constitutively active CheY mutant that mimics the CW-rotation stimulating function. The coordinated switching requires CheZ, which is the phosphatase for CheY-P. Our results suggest that a transient increase and decrease in the concentration of CheY-P caused by a spontaneous burst of its production by the chemoreceptor patch followed by its dephosphorylation by CheZ, which is probably a wavelike propagation in a subsecond timescale, triggers and regulates the coordinated switching of flagellar motors.